Sintilimab maintenance therapy post first-line cytokine-induced killer cells plus chemotherapy for extensive-stage small cell lung cancer - Ma, Baozhen; Zhou, Yu; Shang, Yiman; Zhang, Yong; Xu, Benling; Fu, Xiaomin; Guo, Jindong; Yang, Yonghao; Zhang, Fang; Zhou, Mengyuan; Huang, Hao; Li, Fanghui; et al. (Frontiers in Oncology, 2022)
Despite recent progress in treating advanced non-small cell lung cancer, clinical intervention in extensive-stage small-cell lung cancer (ES-SCLC) remains stagnant. The purpose of this study was to evaluate the clinical efficacy of cytokine-induced killer (CIK) cells combined with cytotoxic chemotherapy, followed by anti-programmed death 1 antibody (sintilimab) maintenance, in ES-SCLC patients. To explore a new method for safe treatment of ES-SCLC patients, thirteen ES-SCLC patients were enrolled between June 2019 and December 2021. All patients received first-line chemotherapy (etoposide plus platinum) combined with CIK cell therapy. Patients who reached a stable disease state or responded well to treatment received sintilimab maintenance treatment. The primary objective of this study was to determine the median overall survival (OS); the secondary objective was to assess the objective response rate (ORR), progression-free survival 1 and 2 (PFS1 was defined as the duration from the signing of informed consent to the date of tumor progression, or death, or the last follow-up. PFS2 was defined as the duration from the first day of sintilimab treatment to the date of tumor progression, death, or the last follow-up.), and adverse reactions. At a 24.1-month follow-up, the median OS was 11.8 (95% confidence interval [CI]: 10.6–13.0) months, median PFS1 was 5.5 (95% CI: 5.0–6.0) months, and the median PFS2 was 2.3 (95% CI: 0.5–4.1) months. The ORR was 76.9% (10/13), the disease control rate was 100% (13/13), and the 20-month survival rate was 41.7%. Eight participants exhibited grade 3 or 4 adverse events after combination therapy. During maintenance treatment with sintilimab, level 3 adverse events occurred in 1 patient (1/9). In conclusion, adding CIK cells to standard chemotherapy regimens, followed by maintenance therapy with sintilimab, may represent a new safe and effective treatment strategy. (ClinicalTrials.gov NCT03983759)